2015
DOI: 10.3109/01612840.2014.978424
|View full text |Cite
|
Sign up to set email alerts
|

Preceptors’ Expectations of Nursing Students’ Preparation before Placement in Psychiatry: Ability and Will to Reflect on and Exercise Knowledge

Abstract: Nursing students must be prepared to provide nursing care regardless of the patient's illness. This requires that nursing education, including clinical placements, strengthen knowledge and skills in mental health nursing. The aim of this qualitative study was to describe 15 preceptors' expectations of nursing students' preparedness before they entered the psychiatric field. Data was collected with focus group interviews and analysed using conventional content analysis. The findings show that preceptors are con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 40 publications
1
8
0
Order By: Relevance
“…Preceptors are concerned about students’ willingness and ability to work in the mental health setting (Kirkbakk‐Fjær et al . ). Participants reported that students’ personal beliefs or lack of knowledge often resulted in negative views of mental health nursing.…”
Section: Resultsmentioning
confidence: 97%
See 4 more Smart Citations
“…Preceptors are concerned about students’ willingness and ability to work in the mental health setting (Kirkbakk‐Fjær et al . ). Participants reported that students’ personal beliefs or lack of knowledge often resulted in negative views of mental health nursing.…”
Section: Resultsmentioning
confidence: 97%
“…Students might be able to better prepare for and improve their confidence by visiting the site before commencing their placement, while educators should assess their personal attitudes and maturity ahead of the placement (Kirkbakk‐Fjær et al . ).
Perhaps they need to come and have a few visits and see how the psych ward actually runs … so that that fear is not there about, “Oh my god, I'm going to be killed, I'm going to a psych unit for a period of time.”
…”
Section: Resultsmentioning
confidence: 97%
See 3 more Smart Citations